2018
DOI: 10.1109/jiot.2018.2840129
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Data Streams With Dynamic Gaussian Mixture Models: An IoT Application in Industrial Processes

Abstract: In industrial Internet of Things applications with sensors sending dynamic process data at high speed, producing actionable insights at the right time is challenging. A key problem concerns processing a large amount of data, while the underlying dynamic phenomena related to the machine is possibly evolving over time due to factors, such as degradation. This makes any actionable model become obsolete and necessary to be updated. To cope with this problem, in this paper we propose a new unsupervised learning alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…As a result, it has been demonstrated that unsupervised ML algorithms embedded in CPS are the key enablers for working towards highly accurate diagnosis and prognosis tools. In another study proposed by the same authors [18], they presented a new unsupervised learning algorithm based on GMM called Gaussian-based dynamic This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: Related Workmentioning
confidence: 99%
“…As a result, it has been demonstrated that unsupervised ML algorithms embedded in CPS are the key enablers for working towards highly accurate diagnosis and prognosis tools. In another study proposed by the same authors [18], they presented a new unsupervised learning algorithm based on GMM called Gaussian-based dynamic This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: Related Workmentioning
confidence: 99%
“…Kullanıcıya ait click verisi analizi [6], saldırı tespit sistemleri [7][8][9], sosyal medya [10][11][12], finansal uygulamalar [13], bilimsel araştırmalar [14], sağlık araştırmaları [15][16][17], mobil uygulamalar [18], nesnelerin interneti (IoT) [19] ve sensor ağ [20,21] gibi pek çok alanda kullanılmaktadır. Nesnelerin interneti konusunun yaygınlaştığı günümüzde uygulama alanlarının daha da artacağını söylemek mümkündür.…”
Section: Akan Veri Kümeleme Yaklaşımlarının Uygulama Alanlarıunclassified
“…In addition, the algorithm operates with very small amounts of data and greatly reduces calculation power to determine whether to modify the model. e algorithm can be evaluated on synthetic data and data stream from a test bed where various operating conditions are detected automatically, with good results in terms of classification precision, sensitivity, and characteristics [2]. Based on trajectory data, regular behaviour of private cars are extracted [3][4][5].…”
Section: Introductionmentioning
confidence: 99%